The Effect Of Trust, Social Media And Electronic Word Of Mouth (E-Wom) On E-Commerce Customer Participation - Ita Apriana Kinas; Dian A.S Parawansa; Muhammad Ismail (SEIKO : Journal of Management & Business, 2023)
The Faculty of Economics and Business, Indonesian Muslim University Makassar batch 2018, this study examines the effect of Trust (Trust), Social Media, Electronic Word of Mouth (E-Wom) on E-Commerce Customer Participation. Utilizing a quantitative methodology, this investigation. Primary and secondary data were used in this study, and they were both obtained by mailing Google Form surveys to 165 FEB students at the Muslim University of Indonesia. SPSS was used in this study’s data processing. Multiple linear was performed in the data analysis process. According to the study’s findings, trust, social media and electronic word of mouth (e-wom) all significantly influenced how many e-commerce customers participated in the Faculty of Economics and Business at Indonesian Muslim University Makassar in 2018. Keywords: electronic word of mouth (e-wom), trust, e-commerce customer participation, social media.